2016
DOI: 10.1182/blood-2015-04-640128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lenalidomide treatment on clonal architecture of myelodysplastic syndromes without 5q deletion

Abstract: Key Points• Lenalidomide treatment has variable transient effects on the clonal architecture of myelodysplastic syndromes without 5q deletion.• Lenalidomide is unlikely to eradicate myelodysplastic clones characterized by combinations of SF3B1, TET2, DNMT3A, and ASXL1 mutations.Non-del(5q) transfusion-dependent low/intermediate-1 myelodysplastic syndrome (MDS) patients achieve an erythroid response with lenalidomide in 25% of cases. Addition of an erythropoiesis-stimulating agent could improve response rate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 40 publications
5
29
0
1
Order By: Relevance
“…Our data confirmed the existence of a linear path of clonal evolution, but importantly, also uncovered previously unrecognized branching evolution leading to the emergence of genetically advanced MDS subclones during disease progression that are capable of mediating drug resistance. Although recently reported in the context of single MDS/CMML cases and other tumor entities, 32,39,[43][44][45][46][47][48][49] the observed frequency of this phenomenon was largely unrecognized in MDS so far. Moreover, we observed that treatment with drugs such as LEN, 5-aza, or temsirolimus was immediately followed by significantly elevated fluctuations in both the oligoclonal BM composition and clinical parameters.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our data confirmed the existence of a linear path of clonal evolution, but importantly, also uncovered previously unrecognized branching evolution leading to the emergence of genetically advanced MDS subclones during disease progression that are capable of mediating drug resistance. Although recently reported in the context of single MDS/CMML cases and other tumor entities, 32,39,[43][44][45][46][47][48][49] the observed frequency of this phenomenon was largely unrecognized in MDS so far. Moreover, we observed that treatment with drugs such as LEN, 5-aza, or temsirolimus was immediately followed by significantly elevated fluctuations in both the oligoclonal BM composition and clinical parameters.…”
Section: Discussionmentioning
confidence: 96%
“…[37][38][39] Our exhaustive analysis of a large cohort of 31 MDS patients in combination with our detection of mutated B cells in long-term xenoengrafted MDS hematopoiesis now provides definitive proof that genetically defined MDS HSC clones frequently contribute to lymphopoiesis. These findings raise important questions about the potential influence of intrinsically aberrant lymphopoiesis on the pathogenesis of MDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a DNMT3A mutation could be predictive of better responses of lower-risk MDS patients without 5q deletion to the lenalidomide treatment. Especially, it was independently related to HI-E [36]. Further prospective studies are mandatory to predict which MDS patients may respond to lenalidomide.…”
Section: Discussionmentioning
confidence: 99%
“…However, an analysis of clonal architecture of non-del(5q) MDS patients who were treated with lenalidomide alone or lenalidomide plus epoetin-β showed that lenalidomide is unlikely to eradicate MDS clones bearing SF3B1 mutations [68]. The telomerase inhibitor imetelstat is another class of drug that is suggested to show preferential effects against myelofibrosis patients with SF3B1 or U2AF1 mutations versus patients without these mutations (complete response rate, 38 versus 4%, p = 0.04) [69].…”
Section: Therapeutic Intervention For Sf3b1 Mutant Malignanciesmentioning
confidence: 99%